Penerapan Model Pembelajaran Mapping untuk Meningkatkan Hasil Belajar IPS Siswa Kelas IV SD Negeri 2 Winning Kabupaten Buton - Suarti Suarti (Jurnal Akademik FKIP Unidayan, 2020)
The purpose of this study was to determine the application of mind mapping models in social studies learning for fourth grade students of SD Negeri 2 Winning, Buton Regency. This research is a type of classroom action research because researchers act directly in research. The research subjects were students in grade IV SDN 2 Winning in Buton Regency with a total of 25 students consisting of 11 male students and 14 female students. Data collection techniques using tests and observations. The research instrument used observation sheets and test questions or evaluation of learning outcomes. The data analysis technique was done in quantitative descriptive and qualitative descriptive. The results showed that before the application of the mind mapping learning model in social studies learning, obtained as many as 5 students (20%) completed and 20 students (80%) had not yet completed and the average grade of 60%. But after learning by applying mind mapping models in cycles I and II obtained data that student learning outcomes improved. The learning outcomes of the first cycle stated that as many as 13 students (52%) had finished and 12 students (48%) had not yet completed and the average grade of 70.24%. Then the results of the second cycle test showed that 22 students (88%) had finished and 3 students (12%) had not yet completed and the average grade of 81.44%. With the increase that occurs in students who have reached 88%, it is stated that the standard of success has reached 75% and is complete.